Sejarah Habib Husein Al-Qadrie dalam Menyebarkan Ajaran Islam di Daerah Pedalaman Kalimantan Barat - Bibi Suprianto (JUSPI (Jurnal Sejarah Peradaban Islam), 2021)
The history of Habib Husein Al-Qadrie in spreading teachings in the interior of West Kalimantan began with four young men who migrated from Tarim Hadramaut Yemen. The four people were suggested by his teacher to spread Islamic teachings outside the city. The four scholars separated and spread Islamic teachings in various regions. Habib Husein Al-Qadrie migrated to Aceh, Betawi, Semarang, Matan (Sukadana) and Mempawah. In spreading the teachings of the Islamic religion, Habib Husein is known to many people about his intelligence and policies in overcoming religion. He became Mufti in the Matan Kingdom (Sukadana) and became Mufti Mempawah in West Kalimantan. Habib Husein Al-Qadrie already had a son who became the Sultanate of Pontianak, with namely Syarief Abdurrahman Al-Qadrie. His son had succeeded in establishing the Sultanate of Pontianak in accordance with the mandate from his father to migrate to the residential area of Sungai Kapuas. This is commandment to continue the spread of Islamic teachings through the Pontianak Sultanate.